Polyglobalide-Based Porous Networks Containing Poly(ethylene glycol) Structures Prepared by Photoinitiated Thiol-Ene Coupling - Savin, Corina L; Peptu, Cristian; Kroneková, Zuzana; Sedlačík, Michal; Mrlik, Miroslav; Sasinková, Vlasta; Peptu, Catalina A; Popa, Marcel; Mosnáček, Jaroslav (Biomacromolecules, 2018)
The high interest in polymers from natural resources prompted us to investigate the use of enzymatically synthesized polyglobalide (PGL) in the preparation of polymer networks with potential applications as biomaterials for drug delivery devices. Polymer networks were obtained under mild conditions by photoinitiated thiol-ene coupling between PGL and a poly(ethylene glycol- co-thiomalate) (PEG-SH) copolymer obtained by polycondensation. The obtained polymer networks were thoroughly characterized by Raman spectroscopy, scanning electron microscopy, titration of thiol groups and elemental analysis. Our study took into consideration the synthesis parameters for the polymer networks, such as the total polymer concentration and the SH/C=C functionality molar ratio. Swelling in both THF and water was assessed, and the potential of the materials for drug delivery was determined. The scanning electron microscopy images showed that the prepared polymer networks may have different morphologies ranging from homogeneous polymer materials to macroporous structures. Additionally, the prepared materials were found to be suitable from a cytotoxicity point of view, enabling their application as biomaterials for drug delivery devices.
Keywords: Animals; Esters; laktony; estery; polyethylenglykoly; 3T3 Cells; Polyethylene Glycols; zvířata; Hydrogels; Mice; sloučeniny síry; Ultraviolet Rays; Sulfur Compounds; Lactones; buňky 3T3; hydrogely; ultrafialové záření; myši